PENGARUH KUALITAS PELAYANAN DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA OTO BANK NAGARI CABANG KOTO BARU - Aldia Rilas; Mayroza Wiska; Fenisi Resty (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2022)
This study was conducted to determine how much influence service quality and satisfaction customers on customer loyalty at Oto Bank Nagari Koto Baru Branch. The purpose of this research was carried out to find out how much influence Service Quality and Customer Satisfaction have on customer loyalty in Oto Bank Nagari Koto Baru Branch. The method in this study is a quantitative method and data collection using a questionnaire. The population in this study were all students of Dharmas Indonesia University as customers at Oto Bank Nagari, the respondents who were used as samples were 93 respondents. Based on the results of the study, it is known that the value of the coefficient. The results of the study prove that the magnitude of the nfluence of service quality on customer loyalty and the absence of nfluence of customer satisfaction on customer loyalty.